2021
DOI: 10.11604/pamj.2021.39.85.26685
|View full text |Cite
|
Sign up to set email alerts
|

Insuffisance rénale chronique et hémodialyse à Lomé: l´hémodialysé et son entourage sont-ils bien informés?

Abstract: L´insuffisance rénale terminale nécessite un traitement de suppléance notamment l´hémodialyse. Avant l´initiation, le patient et son entourage reçoivent des informations sur la maladie rénale et les possibilités de traitement. Ce travail a pour objectif d´évaluer le niveau de connaissance ainsi que l´opinion de l´hémodialysé et de son entourage sur la maladie rénale chronique et les traitements de suppléances rénales. Il s´est agi d´une étude transversale descriptive qui s´est déroulée du 29 juillet au 19 août… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…TCHUENDEM found with the same cohort, a mean age of 44.44 ± 12.35 years with extremes of 16 and 87 years (4). These gures are not very far from those published by TSEVI in Togo, 49.7 ± 13.5 years(5) and FAYE in Senegal 50.49 ± 14.50 years (6), in West Africa. FOUDA in Cameroon found 47.97 ± 13.19 years, in Central Africa(7).…”
contrasting
confidence: 42%
See 1 more Smart Citation
“…TCHUENDEM found with the same cohort, a mean age of 44.44 ± 12.35 years with extremes of 16 and 87 years (4). These gures are not very far from those published by TSEVI in Togo, 49.7 ± 13.5 years(5) and FAYE in Senegal 50.49 ± 14.50 years (6), in West Africa. FOUDA in Cameroon found 47.97 ± 13.19 years, in Central Africa(7).…”
contrasting
confidence: 42%
“…The unemployed and shopkeepers were the most represented, with 21.2% and 14.9% of cases respectively. TSEVI found that the unemployed and shopkeepers were the most numerous in its cohort, with 20 and 21.2% respectively (5). Kidney failure is a reason for redundancy for some patients.…”
Section: Resultsmentioning
confidence: 99%